PENGARUH MEDIA SOSIAL DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK SOPHIE MARTIN DI KOTA KLATEN - Damasita, Verayani Rahma Nur; Nurhidayat , Erwan (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2022)
The rapid development of technology has attracted the attention of researchers to conduct research, especially on the impact of social media and changes in people's lifestyles on purchasing decisions for Sophie Martin products in Klaten City. This study aims to examine the empirical model: The influence of social media and lifestyle on purchasing decisions for Sophie Martin products in the city of Klaten. The research is a survey research, the data collected is secondary data and primary data by taking the people in the city of Klaten as the object of research. Data collection is in the form of a list of questions (questionnaires) both open and closed questions. In this study, it will be known how much influence social media has on purchasing decisions for Sophie Martin products. The results of the study using the IBM SPSS version 28.0 program stated that social media has a very strong influence on purchasing decisions for Sophie Martin products in the city of Klaten as evidenced by the number of consumers who buy and know Sophie Martin products through social media as much as 67.2% which can be seen from the results. research correlation test with a strong degree of correlation between social media and purchasing decisions. While the regression analysis states that lifestyle has no influence on purchasing decisions for Sophie Martin products. While the correlation analysis states that lifestyle affects 59% with the category of moderate degree of correlation.